Researcher Profile: An Interview with Sonya Britt, Ph.D., CFP, AFC - Sonya Britt (Journal of Financial Therapy, 2013)
Sonay Britt, Ph.D., CFP, AFC graduated from Texas Tech University in 2010 with a doctorate in Personal Financial Planning. Her first two degrees are from Kansas State University in Personal Financial Planning (B.S.) and Marriage and Family Therapy (M.S.). and she was the founding president of the Financial Therapy Association and recently retired from the board as past-president. She currently serves on the board of the American Council on Consumer Interests association. Sonya is an associate editor for the Journal of Family and Economic Issues and on the editorial board of the Journal of Financial Therapy and on the international scientific board of the Italian Journal of Sociology of Education.
Keywords: financial therapy; financial planning; financial counseling